Hearing Voices: Why the Academy Needs Clinical Scholarship - Clark D. Cunningham (Washington University Law Quarterly, 1998)
The following Article is a lightly edited transcript of remarks made on October 14, 1995 at the annual meeting of the Central States Law School Association at St. Louis University School of Law. A few hours before my presentation, I learned that Herbert Eastman, director of clinical education at St. Louis University, had died. Herb had been diagnosed with cancer a few months earlier; he was forty-four when he died. Although Herb was unfailingly genial and seemingly mild-mannered, he was, in fact, driven by a fierce passion for justice. Teacher, scholar, advocate-exemplary in each field as if he had but that one trade alone. Herb lived in the split between the academy and the outside world, but moved in the opposite direction of schizophrenia. The voices he heard in the outer world were projected with great force into the inner world of mind. Perhaps the intensity with which he taught, advocated and wrote might have seemed a bit crazed, yet he would have not chosen to live differently even if the reward was a longer life span. And perhaps with those heaven-bound cries forever in his ears, he could not have chosen differently. This essay endeavors to show why the legal academy needs clinical scholars like Herb Eastman.
Keywords: Clinical legal education; Law – Study & amp; teaching; Eastman; Herbert A.; 1951-1995